THE EFFECT OF FACTOR VALUE OF PRODUCTION INDUSTRIAL TEXTILE AND TEXTILE PRODUCTS ON EXPORT AND ITS IMPACT ON GROSS DOMESTIC PRODUCT : PARTIAL LEAST SQUARE APPROACH - Faisal Hasbullah Batubara; Elis Masitoh (Jurnal Ekonomi, 2023)
This study aims to explore the contribution of the dominant factor of textile production in Indonesia to the value of production, export value and gross domestic product. Using monthly data for 5 years of observation and analyzing using the Partial Least Square (PLS) model of empirical and theoretical facts shows something that can be correctly guessed, but the statistics of results are different. The result of analisys show that the Xa - Xd indicator has a positive trend, while Xe and Xf have a negative trend, EV and PV variables have a negative tendency whereas GDP has a positive trend, and are these 3 variables and 1 Latent Variable Dominant Factors having cointegration with each other within the study period.The most dominant indicator is Xb (Value of Investmen) and Xa (Number of Companies) of approximately 100%, then Xc (machine capacity) of 98% and Xe(labor absorption) -95%, then Xf (utility) of -98% Labor absorption contributes negatively to the dominant factor of textile production, meaning that for every increase in the dominant factor of textile production, the absorption of labor is reduced by a contribution of approximately 95%, so its utility is reduced by 98%. Theoretically, the reduced labor absorption must be irritated by the reduced utilization value as well, because the fewer the amount of labor that can be exploited the smaller the level of benefit in the benefit of society. However, other indicators increase with increasing dominance of production.